5c-33=99-c

Simple and best practice solution for 5c-33=99-c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5c-33=99-c equation:



5c-33=99-c
We move all terms to the left:
5c-33-(99-c)=0
We add all the numbers together, and all the variables
5c-(-1c+99)-33=0
We get rid of parentheses
5c+1c-99-33=0
We add all the numbers together, and all the variables
6c-132=0
We move all terms containing c to the left, all other terms to the right
6c=132
c=132/6
c=22

See similar equations:

| 9x-4=6x+4=180 | | 2/5y−4+7−910y= | | -5h+10=-8h+10+3h | | 14x-13=4x+13=6x=2 | | 5x-8=3+5x | | (x^2-5x+8)/x=4 | | -6x+5+2x=5 | | X=7x-3x+18 | | 24+4y/y=11/2 | | 3n×n=4 | | 9+m=m+9 | | 8x+1+5x-4=180 | | o+-20=-19 | | 0.8x+8.3x=-2 | | Y=72m | | 2w-5+95=180 | | k+-13=-7 | | 18=n/2-5 | | 4x^2−8x−20=0 | | 8t-5=8t+9 | | 10x+20=2x-20 | | a4=184a​ =18 | | 6-8(1-3f)=-30 | | 14.95–4.4k=3.9–6.1k | | 4x+54=24 | | 9.6x=3(3-2x) | | (x^2-5x+8)/2=4 | | 96=8b | | 3x-5=7x+5= | | w-8+13=23 | | 8+6t=-4+2t | | -3(4j+2)+j=27 |

Equations solver categories